Case Report: COVID-19 and Ischemic Stroke in A 16-Years-Old Patient - Cynthia; July Kumalawati (Magna Neurologica, 2024)
Background: Recent reports show an increasing trend of ischemic stroke at a young age. Diseases associated with ischemic stroke at a young age, namely hereditary hypercoagulable conditions. Case: In this case a 16-year-old boy with clinical complaints of sudden weakness of the right hand and leg, numbness, loss of appetite, nausea and vomiting. Laboratory tests showed results of increased levels of hemoglobin, hematocrit, erythrocyte count, platelet count, leukocyte count and NLR. The neutrophil-to-lymphocyte ratio (NLR), calculated as a simple ratio between the neutrophil and lymphocyte counts measured in peripheral blood. CT scan examination showed acute infarction in the medial left temporal lobe and old infarction in the left frontal lobe (medial gyrus). Thoracic CT Scan examination showed the results of bilateral pneumonia suggestive of viral. The patient encountered COVID-19. The patient experienced cough and shortness of breath and showed abnormal ABG results, namely respiratory alkalosis, decreased oxygen saturation, fever, increased procalcitonin and increased cardiac markers. Discussion: This case report prompts discussions on various aspects of ischemic stroke in young patients, including the role of COVID-19, hypercoagulable states, hematological abnormalities, and diagnostic challenges, with implications for patient management and future research directions. Conclusion: SARS CoV-2 can affect the nervous system through several mechanisms that cause persistent infection, resulting in neurological diseases, including stroke. Young ischemic stroke is usually hypercoagulable and the most common cause is APS. In this patient, polycythemia was occured,that causes blood flow slows and oxygen supply to the brain is reduced. This can cause ischemic stroke.